Atividade predatória do fungo Duddingtonia flagrans sobre larvas infectantes de estrongilídeos parasitos de equinos na pastagem no sul do Brasil - Almeida, Gisane Lanes de (2009)
Biological control is an alternative method used to reduce the population of parasites through natural antagonist. A promising option of biological control to reduce infective larvae in pasture is the use of nematophagous fungus. The efficacy of the nematophagous fungus Duddingtonia flagrans was tested to control gastrointestinal nematode parasites of horses in field. Ten foals with mean age of 12 months were divided in two groups: five males constituted the treated group and five females constituted the control group. Each group was introduced into a plot formed by mixed pasture with approximately 5 hectares. The treated group received D. flagrans fungus in a concentration of 106 clamidospores kg-¹ body weight, mixed with horse ration, daily, for five months. The control group did not receive the fungus. Faecal egg count (FEC) samples were carried out weekly. Coproculture and collection of pasture were done monthly for larvae counting. No significant difference was observed in the FEC counting and in the number of larvae recovered from coprocultures, where cyathostomes, Strongylus sp. and Trichostrongylus sp. were found. The number of larvae recovered from pasture was significantly lower in the treated group in the last month of treatment, where the percentage reduction was 73.5%. Therefore, the fungus was able to reduce the number of infective larvae in pasture, but this was not reflected in the reduction of parasite infection during treatment (five months).